Economic consequences of populism - Steinbuka, Inna; Xu, Yinglu (University of Latvia, 2020)
This paper is aimed at assessing the potential negative impacts of radicalization and populism on the national economy with a special focus on fiscal policy and international trade. The authors presume that populist governments tend to implement expansionary fiscal policy and advocate protectionism. This research is a synergy of political and economic analysis. The authors describe the EU and Eurozone fiscal trends and risks (public debt and budged deficit) and provide examples of economic commitments of populist governments. They analyse how different definitions of radicalization and populism match with the current trends in populist parties, describe risks of implementing expansionary fiscal policies by left- and right-wing populist governments of some EU member states and provide illustrations of current protectionist movements in the US. The authors conclude that EU supervisory role and control mechanisms are crucial to reduce fiscal risks and preserve stability in Eurozone. Decisive actions of international community and domestic political pressure are the only safeguards against distortive effects of protectionist policies.
Keywords: populism; radicalization; fiscal policy; international trade; Research Subject Categories::SOCIAL SCIENCES::Business and economics